Highly selective cross ketonization of renewable acids over magnesium oxide. Issue 2 (21st December 2022) - Goculdas, Tejas; Deshpande, Siddharth; Zheng, Weiqing; Gorte, Raymond J.; Sadula, Sunitha; Vlachos, Dionisios G.
Abstract : The rising demand for linear alkylbenzene surfactants (LAS) poses an environmental threat as LAS are industrially produced from petroleum using corrosive acid catalysts. Abstract : The rising demand for linear alkylbenzene surfactants (LAS) poses an environmental threat as LAS are industrially produced from petroleum using corrosive acid catalysts. Cross ketonization is a promising route of converting furans and fatty acids to oleo-furansulfonates, precursors for renewable, performance-enhanced LAS replacements. Here, we explore various alkaline earth metals and mixed metal oxides for the cross-ketonization reaction and find that MgO achieves ∼90% yield by minimizing the decarboxylation side reaction. We illustrate the role of molecular structure on the cross-ketonization reaction and the role of complex formation over alkaline-earth metal oxides in minimizing side reactions. We overcome catalyst deactivation by regeneration over multiple runs. This research demonstrates the effectiveness of heterogeneous catalysts for cross ketonization toward developing renewable surfactants.